Symptoms of Anxiety and its Reduction by Leisure Activities during Weekend Program among WICA Players through Non-Formal Education - Iffat Nazir Khan; Shamaila Hamid Mahmud (IJLTP, 2024)
The study contributes to our knowledge of anxiety in community in the light of Pakistan's expanding awareness of anxiety, a comorbid symptom of attention deficit hyperactivity disorder (ADHD). It aims to illuminate the views of teenagers with ADHD on sports and anxiety while providing information on the functions played by parents, neighbors, and society in their lives. The study used a qualitative, descriptive, and case study methods with six participants (three male and three females) who were all WICA (Wasim International Cricket Academy) players during weekend program, through non-formal education, who had their symptoms of anxiety evaluated. Data collection included in-depth interviews conducted by the researcher, focusing on adolescents with ADHD experiencing high levels of anxiety. Results revealed that leisure activities reduced symptoms of anxiety in five of the sample, out of six adolescents during weekend program. This study lays the groundwork for further investigations in the field and emphasizes the importance of addressing the needs of adolescents in society.